Evaluation of pearl millet and mungbean intercropping systems in arid region of Rajasthan (India) - Ram, Kalu; Meena, RS (Bangladesh Journal of Botany, 2015)
A field experiment was conducted during kharif season, 2011 to evaluate different row ratio of pearl millet with mungbean in the arid region of Rajasthan. The treatments comprised of sole pearl millet at 45 cm spacing, one sole mungbean and ten pearl millet with mungbean treatments row in different ratio. The intercropping of pearl millet with mungbean in 1 : 7, followed by 2 : 6 and 1: 3 row ratio produced maximum pearl millet equivalent yield (PMEY), land equivalent ratio (LER), aggresivity , net returns,benefit cost (B : C) ratio and also better nutrient uptake by these treatments compared to sole and other intercropping treatments. Aggressivity values showed that inter crop mungbean did not offer any competition to pearl millet in different row ratio, while relative crowding coefficient (RCC) values indicated was a yield disadvantage in mungbean in all the intercropping system except 1: 7 row ratio. DOI: http://dx.doi.org/10.3329/bjb.v43i3.21616 Bangladesh J. Bot. 43(3): 367-370, 2014 (December)